Daily Fluid Intake Behaviors and Associated Health Effects Among Australian and United States Populations - Sims, Jesse N. L.; Holland, Justin J.; Anderson, Travis; Adams, William M. (Frontiers in Sports and Active Living, 2022)
Minimal data exist exploring intercontinental differences in fluid intake (FI) beliefs and behaviors and the impact on fluid intake practices (i.e., fluid intake volume, beverage type, and timing of fluid intake). Therefore, this study explored the impact that FI beliefs and behaviors had on FI practices among emerging adults living in the United States (USA) and Australia (AUS). A total of 489 individuals (74.5% female; USA, 79.4%; age, 25 ± 6 years completed a 23-item survey between November 2020 and June 2021). Participants detailed their FI practices. FI beliefs were evaluated to determine their contribution to FI behaviors across the day. Multinomial and multiple linear regression analyses explored the association of daily FI beliefs and behaviors across multiple domains. Independent sample t-tests and chi-square analyses were conducted to compare FI practices, beliefs, and behaviors between individuals in the USA and AUS. FI behaviors were significantly different between countries, with the USA more likely to consume fluids to meet a total target volume (β = 1.150, p = 0.036) and consume fluid at the same time as structured daily activities (β = 0.773, p = 0.046) compared to FI alongside food intake. However, there were no differences in the types of beverage consumed (juice, sugar-sweetened beverages, tea, and coffee), total fluid volume, and physical activity (PA) between countries (p > 0.05). Beverage consumption was higher among USA than AUS residents for water, beer, and wine (p < 0.05). Total fluid consumption was greater among males (3,189 ± 2,407 ml) than females (2,215 ± 1,132 ml; β = 3.61, p < 0.001), individuals who regularly consumed fluid during the day to meet a targeted volume (β = 1,728.5, p < 0.001), and those who regularly consumed fluid as a habitual behavior (β = 3.97, p < 0.001) compared to those individuals who only consumed fluid alongside mealtimes (β = 1,041.7, p < 0.001). FI behaviors differed between the USA and AUS; however, total volume consumed, type of beverage consumed, and FI beliefs were similar. FI practices and behaviors appear to be individualized and context-specific among the studied populations.